2021
DOI: 10.3991/ijet.v16i05.21271
|View full text |Cite
|
Sign up to set email alerts
|

A New Project-based Learning Concept in English Writing

Abstract: At present, more international talents are needed. English writing ability is an essential quality for such talents. However, by far the teaching of English writing is faced with some problems, that is, students lack interest and learn passively, teachers’ teaching methods are not diversified enough, and there are insufficient interactions between teachers and students in the classroom. How to improve the effectiveness of the teaching of English writing has become a top priority in the current teaching reform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 11 publications
8
29
0
1
Order By: Relevance
“…e English language distance algorithm needs to determine the similarity of the input language. e mean value of the two terms is the mean of time [0,1]. e correlation formula is as follows: sim(ω1, ω2) � e − aL • 1 2…”
Section: English Distance Similarity Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…e English language distance algorithm needs to determine the similarity of the input language. e mean value of the two terms is the mean of time [0,1]. e correlation formula is as follows: sim(ω1, ω2) � e − aL • 1 2…”
Section: English Distance Similarity Algorithmmentioning
confidence: 99%
“…If wi is included in the semantic vector, Si is taken as 1. If it is not included in the sentence, calculate the similarity according to (1). Obtain the semantic vectors S1 and S2 corresponding to statements T1 and T2.…”
Section: English Distance Similarity Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the students in learning writing face some problems that is, students lack interest and learn passively, teachers' teaching methods are not diversified enough, and there are insufficient interactions between teachers and students in the classroom (Lu, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the findings proved that the use of comic strips project can improve students' writing skills in composing interpersonal texts and indicated that the objectives of this study have been achieved.This finding is relevant to Zulaeha and Marpaung's study (2020), which revealed that PjBL is one of the best practices for improving students' writing skills. English teachers should facilitate their students in completing English writing projects through target setting, motivational giving, as well as positive comments and constructive feedback to help students gradually improve their writing skills(Lu, 2021;Tamburro & Harris, 2016). Also, Shanti and her colleagues (2018) discovered that one of the PjBL model's stagesmonitoring students' progress, is the most significant and crucial step in enhancing students' writing skills.…”
mentioning
confidence: 99%